Clinical Characteristics, Diagnostic Challenges, and Therapeutic Outcomes in Non-eosinophilic Esophagitis Eosinophilic Gastrointestinal Diseases in Comparison with Eosinophilic Esophagitis - Azizollah Yousefi; Saeed Sepehry Vafa; Mina Mirzad; Fatemeh Elham Mahjoub; Behnam Shahsavand; Ebrahim Babaee; Fereshteh Karbasian; Mohammad Nabavi; Mohammad Hasan Bemanian; Sima Shokri; Saba Arshi; Morteza Fallahpour (Iranian Journal of Allergy, Asthma and Immunology, 2026)
Eosinophilic gastrointestinal diseases (EGIDs) are chronic, TH2-mediated conditions. Eosinophilic esophagitis (EoE) is the most common type, while non-EoE EGIDs affect other gut segments. This retrospective study of 111 patients (50 EoE and 61 non-EoE) from 2011 to 2022 compared the clinical aspects of these 2 types. Dysphagia and food impaction dominated in EoE, while abdominal pain, nausea, and diarrhea were more common in non-EoE EGIDs. Atopic comorbidities were frequent. Diagnostic delays>1 year were more common in EoE (72% vs 47.5%). The overall clinical response rate was 88.29%, with most patients using food avoidance (90.99%) and proton pump inhibitors (94.59%). Clinical relapses occurred in 38.88% over the mean follow-up of 4.62 years and were unaffected by therapy type. Failure to thrive was seen in 26.7%, with no significant intergroup difference. This study highlights a prolonged diagnostic delay in EoE vs non-EoE EGIDs. Both groups showed similar, favorable response rates, underscoring a need for greater awareness. Prospective studies with standardized measures are required to optimize management.